How to Speak of Non-meaning? Foucault, Derrida and the Attempt to Escape Hegel through Bataille’s Laughter (Revista Eletrônica Estudos Hegelianos, 2024)
Despite all the profound changes that Foucault’s work underwent during the 1960s, there is one point of criticism that Derrida continually repeats: Foucault would remain in a Hegelian framework. According to Derrida, in his anticipation of Georges Bataille’s transgressive thinking, Foucault may have found the right way to escape dialectics, but in his attempt to synthesize transgression with structuralism in The Order of Things, this possibility threatens to be closed off again. Derrida, for his part, turns Bataille’s transgression in a way that allows for a fundamental critique of the concept of knowledge. From the perspective of this critique, not only does a way out of the dialectical identification of the Other open up, but it can also be seen how many philosophical endeavors that imagine themselves to be beyond Hegel continue to stand in his shadow.